Regulation of Synaptic Extracellular Matrix Composition Is Critical for Proper Synapse Morphology - Kurshan, Peri T. (Society for Neuroscience, 2014)
Synapses are surrounded by a layer of extracellular matrix (ECM), which is instrumental for their development and maintenance. ECM composition is dynamically controlled by proteases, but how the precise composition of the ECM affects synaptic morphology is largely unknown. Through an unbiased forward genetic screen, we found that Caenorhabditis elegans gon-1, a conserved extracellular ADAMTS protease, is required for maintaining proper synaptic morphology at the neuromuscular junction. In gon-1 mutants, once synapse formation is complete, motor neuron presynaptic varicosities develop into large bulbous protrusions that contain synaptic vesicles and active zone proteins. A concomitant overgrowth of postsynaptic muscle membrane is found in close apposition to presynaptic axonal protrusions. Mutations in the muscle-specific, actin-severing protein cofilin (unc-60) suppress the axon phenotype, suggesting that muscle outgrowth is necessary for presynaptic protrusions. gon-1 mutants can also be suppressed by loss of the ECM components collagen IV (EMB-9) and fibulin (FBL-1). We propose that GON-1 regulates a developmental switch out of an initial “pro-growth” phase during which muscle arms grow out and form synapses with motor neuron axons. We postulate that this switch involves degradation or reorganization of collagen IV (EMB-9), whereas FBL-1 opposes GON-1 by stabilizing EMB-9. Our results describe a mechanism for regulating synaptic ECM composition and reveal the importance of precise ECM composition for neuronal morphology and synapse integrity.